As reminiscências da morte: espiritualidade e morte no budismo tibetano em diálogo com a psicologia ocidental - Donadon, Felipe (2021)
This research aims to provide a reflection on the perception of death within Geluk Tibetan Buddhism, exploring themes such as precious human life and the implication of moral practice. In addition, it seeks a form of dialogue with Western psychology, in order to better exemplify the difficulties that end up being faced by both professionals and patients, in the proximity of death. Thus, there is an exchange of perspectives on how these two fields of knowledge can contribute to a reinterpretation of generally negative attitudes towards the end of life, such as denial and fear. Therefore, it considers an interface between the interpretations and principles that guide Buddhist conceptions about dying, and the apprehensions and feelings, within a bias of psychological understanding, which are present in the way we deal with this theme.(AU)